Floods in a Megacity: Geospatial Techniques in Assessing Hazards, Risk and Vulnerability - Dewan, Ashraf (Springer, 2013)
Flooding is one of the most devastating natural hazards in the world. Available records suggest that both flood frequency and severity are on the rise and this is likely to worsen in the context of climate change. As population, infrastructure and poverty grow rapidly in developing countries, particularly in urban agglomerations of 10 million people or more, floods could cause widespread devastation, economic damage and loss of life. Assessment of vulnerability and risk from naturally occurring phenomena is therefore imperative in order to achieve urban sustainability. This book uses geospatial techniques to evaluate hazards, risk and vulnerability at a metropolitan scale in a data-scarce country. An empirical study was performed using remote sensing, GIS and census data. This research offers a new approach to mapping population, infrastructures and communities at risk which can greatly contribute to the deeper understanding of flood disasters in a rapidly expanding megacity. Examples shown in this book are from Dhaka Megacity, however, the techniques and methods can easily be implemented in medium to large cities of similar characteristics.